Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Overloaded! Critical revision and a new conceptual approach for snow indicators in ski tourism - B. Abegg; S. Morin; O. C. Demiroglu; H. François; M. Rothleitner; U. Strasser (International Journal of Biometeorology, 2021)
Indicators are widely used in climate variability and climate change assessments to simplify the tracking of complex processes and phenomena in the state of the environment. Apart from the climatic criteria, the snow indicators in ski tourism have been increasingly extended with elements that relate to the technical, operational, and commercial aspects of ski tourism. These non-natural influencing factors have gained in importance in comparison with the natural environmental conditions but are more difficult to comprehend in time and space, resulting in limited explanatory power of the related indicators when applied for larger/longer scale assessments. We review the existing indicator approaches to derive quantitative measures for the snow conditions in ski areas, to formulate the criteria that the indicators should fulfill, and to provide a list of indicators with their technical specifications which can be used in snow condition assessments for ski tourism. For the use of these indicators, a three-step procedure consisting of definition, application, and interpretation is suggested. We also provide recommendations for the design of indicator-based assessments of climate change effects on ski tourism. Thereby, we highlight the importance of extensive stakeholder involvement to allow for real-world relevance of the achieved results.

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

Receptor-independent sensitization of the adenylyl cylase after chronic treatment with cyclosporine A - G. Simonis; T. Christ; S. K. Bährle; M. Pena; S. P. Schoen; R. Marquetant; U. Ravens; R. H. Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Dual mechanism of autoregulation of protein kinase C in myocardial ischemia - Gregor Simonis; Steffen P. Schoen; Martin U. Braun; Stefan Lichte; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2007)

Regulation of protein kinase C isozymes in volume overload cardiac hypertrophy - Martin U. Braun; Paul LaRosée; Gregor Simonis; Mathias M. Borst; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2004)